Mammalian-adaptive mutation NP-Q357K in Eurasian H1N1 Swine Influenza viruses determines the virulence phenotype in mice - Wenfei Zhu; Zhaomin Feng; Yongkun Chen; Lei Yang; Jia Liu; Xiyan Li; Suli Liu; Lijuan Zhou; Hejiang Wei; Rongbao Gao; Dayan Wang; Yuelong Shu (Emerging Microbes and Infections, 2019)
ABSTRACTIt has recently been proposed that the Eurasian avian-like H1N1 (EA H1N1) swine influenza virus (SIV) is one of the most likely zoonotic viruses to cause the next influenza pandemic. Two main genotypes EA H1N1 viruses have been recognized to be infected humans in China. Our study finds that one of the genotypes JS1-like viruses are avirulent in mice. However, the other are HuN-like viruses and are virulent in mice. The molecular mechanism underlying this difference shows that the NP gene determines the virulence of the EA H1N1 viruses in mice. In addition, a single substitution, Q357K, in the NP protein of the EA H1N1 viruses alters the virulence phenotype. This substitution is a typical human signature marker, which is prevalent in human viruses but rarely detected in avian influenza viruses. The NP-Q357K substitution is readily to be occurred when avian influenza viruses circulate in pigs, and may facilitate their infection of humans and allow viruses also carrying NP-357K to circulate in humans. Our study demonstrates that the substitution Q357K in the NP protein plays a key role in the virulence phenotype of EA H1N1 SIVs, and provides important information for evaluating the pandemic risk of field influenza strains.